Pengaruh Budaya Organisasi, Lingkungan Kerja, dan Gaya Kepemimpinan terhadap Loyalitas : (Studi pada Relawan Mengajar Komunitas Jendela Jakarta) - Shinta Aprilia Dewanti; Widi Wahyudi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the influence of organizational culture, work environment, and leadership style on loyalty in Volunteers Teaching of the Jakarta Window Community. Sampling in this study used the slovin formula for 86 respondents. Data was collected through a questionnaire with a Likert scale processed using Microsoft Excel 2013 and SPSS version 22. The research method used is multiple linear regression. The results of this study show that Organizational Culture has a significant effect on Loyalty, while Work Environment and Leadership Style have no effect and are not significant to Loyalty.